2014
DOI: 10.1186/1756-3305-7-381
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi transmission in a Colombian Caribbean region suggests that secondary vectors play an important epidemiological role

Abstract: BackgroundColombia, as part of The Andean Countries Initiative has given priority to triatomine control programs to eliminate primary (domiciliated) vector species such as Rhodnius prolixus and Triatoma dimidiata. However, recent events of Trypanosoma cruzi transmission in localities where R. prolixus and T. dimidiata are not present suggest that other species are involved in the T. cruzi transmission cycle.MethodsWe studied T. cruzi transmission on Margarita Island, located on the Magdalena River in the Colom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 49 publications
6
34
0
1
Order By: Relevance
“…Recently, abundance of wild triatomines in five municipalities on Margarita Island, located on the Magdalena River in the Colombian Caribbean region, were reported by Cantillo- Barraza et al (2014). This locality was not included in our study.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, abundance of wild triatomines in five municipalities on Margarita Island, located on the Magdalena River in the Colombian Caribbean region, were reported by Cantillo- Barraza et al (2014). This locality was not included in our study.…”
Section: Discussionmentioning
confidence: 86%
“…However, recent studies have suggested its epidemiological relevance in the lowland Caribbean region of Colombia and the eastern Colombian plains [4, 5, 10, 42]. In a recent study [15], our group discussed the vectorial relevance of T. maculata based on a) the household-invading behaviour of infected adults, b) transmission in children less than fourteen years old, and c) an epidemiological association between the presence of this species in houses and human seropositivity [10, 15]. The present work provides new evidence supporting this argument.…”
Section: Discussionmentioning
confidence: 99%
“…The population is approximately 30,000 inhabitants, and the economy depends on subsistence agriculture. Previous studies performed in Talaigua Nuevo and Mompós, reported the presence of infected household-invading T. maculata and R. pallescens [6, 15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…En este contexto, es necesario centrar la atención en el orden de los marsupiales y el género Didelphis, el cual es reconocido por su comportamiento sinantrópico, ya que visita o anida en el peridomicilio o en el domicilio en zonas rurales o urbanas, lo cual lo expone a picaduras de triatominos silvestres o domésticos (10,12,30,31).…”
unclassified